Context Dependent Communication and Its Effects on Employee Needs Fulfillment, Creative Processes, and Well-Being - Mariam, Misha (My University, 2021)
Communication with employees is a prime influence mechanism through which authority figures affect important individual and organizational outcomes. In this dissertation, I argue that the communication style of authority figures is an important determinant of employee need fulfillment, creative processes, and emotional well-being. To explore the effects of different communication styles, I use a context dependence approach, which captures the degree to which an individual uses contextual cues in communication to convey and understand meaning. In the first chapter, I present a theoretical model explicating how a leader’s high versus low context-dependent communication style can facilitate or thwart the fulfillment of employee psychological needs. In the second chapter, I theorize how the communication style of managers affects employee creative processes engagement, and emotional well-being, and conduct a field study and two experimental studies to empirically examine the theoretical model.
Thesis (Ph.D.)--University of Washington, 2021
Keywords: Communication; Employee well-being; Leadership; Organizational behavior; Management; Business administration